Побудова моделей структурного типу задля ідентифікації вимірів потенціалу стратегічних змін виробничо-економічних систем - Ладонько, Л.С. (Економіка природокористування і охорони довкілля, 2014)
Статтю присвячено визначенню сутності та змісту такої багатокомпонентної системи, як промисловий потенціал, а також удосконаленню його структури, застосуванню комплексного методичного підходу до визначення складу та ієрархії його елементів,
що уможливлює прийняття оптимізаційних управлінських рішень щодо визначених пріоритетів розвитку промислового потенціалу. The article is devoted to defining the nature and content of multicomponent system – industrial capacity; improvement of the structure of industrial capacity; application of complex methodological approach to determine the composition and hierarchy of its elements, which enables optimization of administrative decision-making on development of defined priorities of industrial capacity. The changes, taking place in the national economy, require searching and working out of new approaches and management techniques, disclose potential opportunities for the functioning of industrial and economic systems and the further development of industrial potential of Ukraine. Thus, it is necessary to form a stable resource-functional system, and improve the overall existing rules and principles of accumulation of innovation potential and effective mechanisms for its rational usage. This will provide organizational and economic conditions for the deployment of self-development and self-organization processes of industrial production in Ukraine under resource constraints. It should be noted that the current stage of development of Ukraine’s economy is characterized by a considerable rearrangement of sources and resources, reserves and capabilities that determine growth of economy. It deals primarily with providing of innovative orientation of economic growth. Results of the assessment limits of the national economy – of its industrial potential (IP) suggest the urgent need to gain attention to a variety of technological, social, organizational and administrative innovations. It is also necessary to study the scientific equipping of
industry and knowledge intensity of its production as an integral component of the strategic industrial growth and sustainable development. Usage of dynamic simulation model of multi-economic system in the implementation of management technologies of industrial potential development will allow analysing differently directed aspects of the industrial and economic processes and ones of functioning of complex industrial and economic systems. In this case, the immediate issues are as follows: implementation of efficient distribution of resources and reserves, establishing proportions in production; solving the major tasks of restructuring the industrial potential; consideration of the most
important factors influencing the operation of the national industry and effectiveness of IP management; identification of priority ways for the effective transformation of limited resources in the final product and the adoption and implementation of the best management decisions in order to achieve the strategic goals of the industry and provide a sufficient level of economic security.